On the interpretation of noun compounds: Syntax, semantics, and entailment. (28th May 2013) - NAKOV, PRESLAV
Abstract: We discuss the problem of interpreting noun compounds such as colon cancer tumor suppressor protein, which pose major challenges for the automatic interpretation of English written text. We present an overview of the more general process of compounding and of noun compounds in particular, as well as of their syntax and semantics from both theoretical and computational linguistics viewpoint with an emphasis on the latter. Our main focus is on computational approaches to the syntax and semantics of noun compounds: we describe the problems, present the challenges, and discuss the most important lines of research. We also show how understanding noun compound syntax and semantics could help solve textual entailment problems, which would be potentially useful for a number of NLP applications, and which we believe to be an important direction for future research.